Molecular characterization of contact urticaria in patients with melon allergy. (1st March 2014) - Gandolfo‐Cano, M.; Bartra, J.; González‐Mancebo, E.; Feo‐Brito, F.; Gómez, E.; Bartolomé, B.; Muñoz‐García, E.; Sanz Maroto, A.; Vivanco, F.; Cuesta‐Herranz, J.; Pastor‐Vargas, C.
Summary: Background: The relevance of contact allergy to plant‐related food has recently emerged. Oral allergy syndrome is one of the most characteristic symptoms of fruit allergy, although it also causes systemic reactions. Plant‐food allergy is increasing at the same time as pollen allergy, and fruit‐induced allergic contact urticaria could be rising as well. Objectives: The present study was carried out in order to investigate whether one particular primary melon‐peel allergen is responsible for contact urticaria. Methods: Fourteen patients presenting with contact urticaria after touching melon peel were evaluated. A melon‐peel extract was prepared and analysed by immunoblotting using the patients' sera. Molecular characterization of IgE‐binding bands was performed using mass spectrometry. Melon‐peel lipid transfer protein (LTP) was purified. Inhibition studies and contact challenge with the protein were performed to confirm IgE reactivity to the purified allergen. Results: An IgE‐binding band of ~8–9 kDa was observed in an immunoblotting assay with all the patients' sera and was identified as an LTP. The melon‐peel LTP was purified in two chromatography steps. Inhibition studies confirmed LTP as a major allergen in patients with melon‐peel contact urticaria. Contact challenge with melon‐peel LTP was performed in five patients, all of whom had positive results, exhibiting itchy erythema and hives in the area of contact. Conclusions: This study confirmed our previous findings that melon‐peel LTP is a major allergen and is responsible for contact allergy. This knowledge may be used to improve both diagnosis and treatment of patients allergic to melon.